Development of an optimal corporate real estate framework for allocation of office space for central government departments in Gaborone, Botswana. - Daman, Aristocrat Babaki (My University, 2013)
The unpredictable economic ups and downs, competition and advancement in technology has seen organisations that hold a great deal of real estate (RE) taking greater interest in the way their Corporate Real Estate (CRE) is managed: with the aim of reducing costs and making sure organisations occupy the right amount of space that is flexible to their changing needs. Public sector (PS) organisations are no exception, with tight budgetary constraints and calls for improved accountability in the use of public resources has seen CRE gain strategic importance. Governments have introduced Corporate Real Estate management (CREM) reforms, giving birth to establishment of RE management departments or subsidiaries and outsourcing of certain RE functions to experts in the private sector. PS organisations have replicated similar strategies to those applied in the private sector such as disposal of surplus property to unlock tied up capital, sale and lease back of property, collocation and portfolio management as value adding mechanisms to improve performance of their real estate. The main aim of CREM is to ensure that the properties occupied by organisations support their core operations. CREM is a discipline that has received a great deal of attention from organisations in the developed world due to pressure to stay competitive and improve shareholder value. CREM is relatively a new concept in developing countries and has not been studied at all in Botswana. The aim of this research report is to explore the current CRE management practices in Central Government Departments (CGD) in Botswana, and how it impacts on efficient use of office space compared to similar sized Private sector and Parastatal organisations. The intention of this research report is to develop CRE framework that will aid in the utilisation of office in government departments. Data was collected through semi structured interviews, open and closed end questionnaires administered to CRE professionals in public and private institutions. The Report recommends that Central Government Departments establish formal CRE units and the current CRE managers must go for further training in Real Estate management disciplines to improve their expertises in the field. Central Government Departments must take cognisance of the existing national office occupancy rate of 9m2 per office space per person and benchmark the use of their occupancy levels against it. It is recommended that CRE managers introduce more open plan office space layouts to improve efficiency in space occupation. The ratio cellular or enclosed to open plan offices is recommended at a rate of 1: 9. Further investigation is required to establish office occupancy densities across the three sectors using the total number of offices occupants and total useable floor area. It is recommended that the future research adopts a comparative approach that is based on size and similar functions of the organisations. KEYWORDS: Corporate Real Estate Management; Public Sector, office space use and allocation.